Genotype and Phenotype Correlations in 417 Children With Congenital Hyperinsulinism - Snider, K. E. (Endocrine Society, 2013)
CONTEXT: Hypoglycemia due to congenital hyperinsulinism (HI) is caused by mutations in 9 genes. OBJECTIVE: Our objective was to correlate genotype with phenotype in 417 children with HI. METHODS: Mutation analysis was carried out for the ATP-sensitive potassium (KATP) channel genes (ABCC8 and KCNJ11), GLUD1, and GCK with supplemental screening of rarer genes, HADH, UCP2, HNF4A, HNF1A, and SLC16A1. RESULTS: Mutations were identified in 91% (272 of 298) of diazoxide-unresponsive probands (ABCC8, KCNJ11, and GCK), and in 47% (56 of 118) of diazoxide-responsive probands (ABCC8, KCNJ11, GLUD1, HADH, UCP2, HNF4A, and HNF1A). In diazoxide-unresponsive diffuse probands, 89% (109 of 122) carried KATP mutations; 2% (2 of 122) had GCK mutations. In mutation-positive diazoxide-responsive probands, 42% were GLUD1, 41% were dominant KATP mutations, and 16% were in rare genes (HADH, UCP2, HNF4A, and HNF1A). Of the 183 unique KATP mutations, 70% were novel at the time of identification. Focal HI accounted for 53% (149 of 282) of diazoxide-unresponsive probands; monoallelic recessive KATP mutations were detectable in 97% (145 of 149) of these cases (maternal transmission excluded in all cases tested). The presence of a monoallelic recessive KATP mutation predicted focal HI with 97% sensitivity and 90% specificity. CONCLUSIONS: Genotype to phenotype correlations were most successful in children with GLUD1, GCK, and recessive KATP mutations. Correlations were complicated by the high frequency of novel missense KATP mutations that were uncharacterized, because such defects might be either recessive or dominant and, if dominant, be either responsive or unresponsive to diazoxide. Accurate and timely prediction of phenotype based on genotype is critical to limit exposure to persistent hypoglycemia in infants and children with congenital HI.